Increased apoptosis, reduced Wnt/β-catenin signaling, and altered tail development in zebrafish embryos exposed to a human-relevant chemical mixture. (February 2021) - Smirnova, Anna; Mentor, Anna; Ranefall, Petter; Bornehag, Carl-Gustaf; Brunström, Björn; Mattsson, Anna; Jönsson, Maria
Abstract: A wide variety of anthropogenic chemicals is detected in humans and wildlife and the health effects of various chemical exposures are not well understood. Early life stages are generally the most susceptible to chemical disruption and developmental exposure can cause disease in adulthood, but the mechanistic understanding of such effects is poor. Within the EU project EDC-MixRisk, a chemical mixture (Mixture G) was identified in the Swedish pregnancy cohort SELMA by the inverse association between levels in women at around gestational week ten with birth weight of their children. This mixture was composed of mono-ethyl phthalate, mono-butyl phthalate, mono-benzyl phthalate, mono-ethylhexyl phthalate, mono-isononyl phthalate, triclosan, perfluorohexane sulfonate, perfluorooctanoic acid, and perfluorooctane sulfonate. In a series of experimental studies, we characterized effects of Mixture G on early development in zebrafish models. Here, we studied apoptosis and Wnt/β-catenin signaling which are two evolutionarily conserved signaling pathways of crucial importance during development. We determined effects on apoptosis by measuring TUNEL staining, caspase-3 activity, and acridine orange staining in wildtype zebrafish embryos, while Wnt/β-catenin signaling was assayed using a transgenic line expressing an EGFP reporter at β-catenin-regulated promoters. We found that Mixture G increased apoptosis, suppressed Wnt/β-catenin signaling in the caudal fin, and altered the shape of the caudal fin at water concentrations only 20–100 times higher than the geometric mean serum concentration in the human cohort. These findings call for awareness that pollutant mixtures like mixture G may interfere with a variety of developmental processes, possibly resulting in adverse health effects. Highlights: A human-relevant chemical mixture induced apoptosis in zebrafish embryos. The mixture reduced Wnt/β-catenin signaling in the embryonic caudal fin. The shape of the caudal fin was altered in embryos exposed to the mixture. The results indicate that the mixture interferes with basic developmental processes.